Respons Muhammadiyah dan Nadlatul Ulama Terhadap Petik Laut di Desa Brondong Lamongan Jawa Timur - Azwan Halim Febriansyah; Hamid Nasuki (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research aims to analyze the response of Muhammadiyah and Nahdlatul Ulama to the Petik Laut tradition in Brondong Village, Lamongan, East Java. The objectives of this study are to uncover and introduce local history, explain the responses of the Muhammadiyah and Nahdlatul Ulama community organizations, and understand the role of religion in the transformation of the Petik Laut tradition. This research employs qualitative methods and an anthropological approach. The data was collected through observation, interviews, and various relevant literature.The results of this study indicate that Muhammadiyah and Nahdlatul Ulama play a significant role in strengthening faith and understanding of religion. Both organizations are concerned with correcting previous understandings that have deviated from religious teachings and have realigned these through da'wah (Islamic preaching). Nowadays, Muhammadiyah and Nahdlatul Ulama have successfully enhanced faith and understanding, which is evident in the Petik Laut activities that now incorporate various religious events. This research is expected to enrich knowledge, preserve and maintain the Petik Laut tradition, and provide information to enthusiasts and observers about the Petik Laut tradition in the Lamongan area.